PENANAMAN NILAI-NILAI ASWAJA AN-NAHDLIYAH PADA SISWA MTS AL-QUDSIYAH KLOTOK PLUMPANG TUBAN - As’idatin Mu’asyaroh; Syamsu Madyan; Adi Sudrajat (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The planting of Aswaja an-Nahdliyah values in students is an important step so that students have an Islamic, tolerant and moderate character to face a life of many differences and opinions. Students of MTs Al-Qudsiyah are mostly from the village, some of them live in the hut of Al-Qudisyah Foundation. With such conditions there are still many students who lack knowledge about the teachings of Islam Ahlussunnah Wal Jama'ah. The focus of the research discussed the values of Aswaja an-Nahdliyah instilled in students, the process of planting these values and supporting factors and inhibitory factors in the process of equaling the value. Therefore, researchers use a type of qualitative descriptive approach research. The result of this study that the values of Aswaja an-Nahdliyah instilled are the values of alum, tawazun, tasamuh, and amar ma'ruf nahi munkar. Stages used in the process of planting values aswaja an-nahdliyah through Providing Knowledge Through Learning Aswaja, Habituation, Interaction/communication. For the supporting factors are teachers, students, and boarding schools. The inhibitory factor is the background of students who do not know at all about Aswaja an-Nahdliyah.